The Expansion and elaboration of the category personality disorders in South Africa 1948-1982 - Laurenson, Helen (Department of Psychology, 2014)
This archival study tracks the expansion and elaboration of the category personality disorders in South Africa from 1948 to 1982. Valkenberg Hospital patient files, official documents and professional publications are triangulated with interviews with clinicians. Previous findings that the diagnosis was applied primarily to white, and to a lesser extent coloured, patients in both the early and late 20th century are confirmed. The thesis argues that the expansion and elaboration of the category personality disorders occurred in interactional fashion both from the top down (via the state and the psy-professions) and from the bottom up (in interactions between clinicians and patients). It was linked to the professionalization of the psy-professions articulating with the state's need to manage the dangerous individual in the context of fears about white degeneration.